IDENTIFIKASI POTENSI INTERAKSI OBAT PADA PASIEN HIPERTENSI : STUDI RETROSPEKTIF RESEP POLIFARMASI DI APOTEK KARYA SEHAT PURWOKERTO - Ikhwan Yuda Kusuma; Peppy Octaviani Dian Megasari; Linda Sukiatno (Viva Medika, 2018)
ABSTRACT Hypertension is public health problem common in developing countries. Basic health research in 2013, the prevalence of hypertension in Indonesia is 26.5% with the largest proportion in Central Java (57.89%). Outpatient of hypertension is tend to require two or more drugs (polypharmacy), combination antihypertension drugs or non antihypertension drugs when accompanied by coexisting illness. Polypharmacy can significantly increase the risk of drug interactions and its an important factor in drug related problems that may affect patient outcome therapy. This study aims to determine the potential drug interactions in a patient's prescription in Karya Sehat Pharmacy Purwokerto. The method of this study was retrospective observational (March-May 2018). Data were analyzed descriptively using Stockley's Drug Interaction, Drug Interaction Facts, www.drugs.com database and Medscape Drug Interactions Checker. The results obtained by looking at the name of the drug listed in the prescription without considering the rules of use, drug dosage and the patient condition was showed potential drug interactions in Karya Sehat Pharmacy Purwokerto was 68.35% (n = 158 samples). The most mechanism pattern is pharmacodinamic interaction (58,89%) and the most severity is moderate (65,74%). Keywords: hypertension, polypharmacy, pharmacy, potential drug interactions